On Homomorphism of Valuation Algebras (Communications in Mathematical Research, 2021)
In this paper, firstly, a necessary condition and a sufficient condition for anisomorphism between two semiring-induced valuation algebras to exist are presentedrespectively. Then a general valuation homomorphism based on different domainsis defined, and the corresponding homomorphism theorem of valuation algebra isproved.
Keywords: homomorphism; valuation algebra; semiring.